Influenza vaccine effectiveness against hospitalisation due to laboratory-confirmed influenza in children in England in the 2015–2016 influenza season – a test-negative case–control study. (2019) - Boddington, N. L.; Warburton, F.; Zhao, H.; Andrews, N.; Ellis, J.; Donati, M.; Pebody, R. G.
Abstract: England has recently started a new paediatric influenza vaccine programme using a live-attenuated influenza vaccine (LAIV). There is uncertainty over how well the vaccine protects against more severe end-points. A test-negative case–control study was used to estimate vaccine effectiveness (VE) in vaccine-eligible children aged 2–16 years of age in preventing laboratory-confirmed influenza hospitalisation in England in the 2015–2016 season using a national sentinel laboratory surveillance system. Logistic regression was used to estimate the VE with adjustment for sex, risk-group, age group, region, ethnicity, deprivation and month of sample collection. A total of 977 individuals were included in the study (348 cases and 629 controls). The overall adjusted VE for all study ages and vaccine types was 33.4% (95% confidence interval (CI) 2.3–54.6) after adjusting for age group, sex, index of multiple deprivation, ethnicity, region, sample month and risk group. Risk group was shown to be an important confounder. The adjusted VE for all influenza types for the live-attenuated vaccine was 41.9% (95% CI 7.3–63.6) and 28.8% (95% CI −31.1 to 61.3) for the inactivated vaccine. The study provides evidence of the effectiveness of influenza vaccination in preventing hospitalisation due to laboratory-confirmed influenza in children in 2015–2016 and continues to support the rollout of the LAIV childhood programme.